Synthetic studies in the higher terpenes. - Rushton, J (1960)
The various groups into which the triterpenes are divided are defined and emphasis is placed on the structural relationships which exist between these groups. A brief description is given of the methos used in teh determination of the structures of triterpenes with articular reference to &beta-amyrin; (I), a member of the oleanane (II) group. Recent progress in the problems of biogenesis and the total synthesis of triterpenes is reviewed. [To continue reading the abstratc please see pdf]